2021
DOI: 10.1038/s41390-021-01779-x
|View full text |Cite
|
Sign up to set email alerts
|

Language function following preterm birth: prediction using machine learning

Abstract: Background Preterm birth can lead to impaired language development. This study aimed to predict language outcomes at 2 years corrected gestational age (CGA) for children born preterm. Methods We analysed data from 89 preterm neonates (median GA 29 weeks) who underwent diffusion MRI (dMRI) at term-equivalent age and language assessment at 2 years CGA using the Bayley-III. Feature selection and a random forests classifier were used to differentiate typical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 63 publications
0
12
1
1
Order By: Relevance
“…Our findings bear significance in that they demonstrate a robust association between DTI measures and language outcomes, independent of both clinical and social risk factors. This association stands in contrast to previous DTI studies which only controlled for clinical factors 26, 39, 40 . Social factors are widely acknowledged as potent predictors of language outcomes 10, 11 , and this was again validated in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings bear significance in that they demonstrate a robust association between DTI measures and language outcomes, independent of both clinical and social risk factors. This association stands in contrast to previous DTI studies which only controlled for clinical factors 26, 39, 40 . Social factors are widely acknowledged as potent predictors of language outcomes 10, 11 , and this was again validated in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, accurately quantifying language development at 2 years is inherently challenging, as evidenced by the limited association between the cognitive and language outcomes at 2 years and later childhood scores in prior studies 50,51 . In contrast, Valavani et al (2021) developed a machine learning model combining clinical factors and neonatal diffusion MRI measures that achieved a higher balanced accuracy of 91% for predicting language deficits at 2 years corrected age in preterm infants 42 . He et al 52 used deep learning and a multimodal MRI approach that included DTI and resting state functional MRI to achieve 88% balanced accuracy in predicting language deficits at age 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently become popular to directly train deep-learning-based classifier algorithms to turn raw signals into high-level categorical outputs, such as diagnostic 54 , 55 or clinical outcomes 41 , 56 , 57 . A direct clinical diagnostic prediction from the raw data could have been used in our context as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicate a strong linear relationship between DWMA signal and microscopic white matter alterations that are consistent with diffuse white matter gliosis ( Galinsky et al, 2020 ; Griffith et al, 2012 ; Volpe, 2009 ) and, considering the published evidence presented above, underscore its significance as a biomarker of later neurodevelopmental impairment. Studies in infants born very preterm have reported that several regional microstructural metrics are associated with neurodevelopmental deficits at 2 to 3 years corrected age ( Ball et al, 2017 ; Parikh, 2016 ; Valavani et al, 2021 ; Vassar et al, 2020 ). We recently examined the combination of DWMA with structural and functional connectivity and clinical factors and demonstrated that such a multimodal approach was more accurate than individual modalities at predicting cognitive, language, and motor deficits at age two ( He et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%